COLLEGE STUDENTS’ CHALLENGES OF ONLINE LEARNING THROUGH ZOOM APPLICATION DURING COVID-19 PANDEMIC - Ervina Rahmatul Annisa; Fauzi Miftakh Miftakh; Putri Kamalia Hakim Kamalia Hakim (Linguistik : Jurnal Bahasa dan Sastra, 2021)
Covid-19 has been labeled a pandemic by the World Health Organization as a current hazard to humanity. This epidemic has successfully caused the global shutdown of a variety of activities in this world, including educational activities. Resulting in massive crisis-response migration of institutions to online learning as the educational platform was discussed. The present interview study reports on two college students' challenges of online learning through the Zoom Application. Semi-structured interviewing was designed to elucidate the students’ voices of online learning challenges during the COVID-19 pandemic. The data garnered from online interviewing were transcribed and interpreted using thematic content analysis.